Of crofters, Celts and claymores: the Celtic Magazine and the Highland cultural nationalist movement, 1875–881. Issue 243 (6th May 2015) - Stewart, Ian B.
Abstract: This article examines the cultural nationalist movement in the Scottish Highlands during the period 1875–88, through the lens of the Celtic Magazine, a source which has been overlooked by historians. The cultural nationalist movement resulted from the intertwining of the crofters' land reform movement with a Celtic cultural revival. It was propelled by intellectuals who promoted the distinctive Celtic nature of the Highlands and demanded recognition from the government. An imagined Highland nation, distinct from the rest of Scotland, arose from the cultural nationalist movement but fitted within a wider 'unionist‐nationalist' identity.